2021
DOI: 10.5194/acp-2021-585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential new tracers and their relative emission factors for burning household waste in stoves

Abstract: Abstract. The production and use of plastics increases rapidly as they are widely used in packaging, construction materials, furniture, foils, etc. As a consequence of their widespread use and often disposable character, vast streams of plastic wastes are continuously generated, a considerable fraction of which are combusted in households worldwide. In this paper, various types of commonly used plastics (PE, PET, PP, PU, PVC, PS, ABS), as well as treated wood samples (LDF) and firewood were combusted separatel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The observed TPB levels in Dhaka were similar in magnitude to prior studies in South Asia, including Kathmandu, Nepal (250−2900 pg m −3 ); 19 Lumbini, Nepal (570−4000 pg m −3 ); 20 Raipur, India (80−15 400 pg m −3 ); 45 Chennai, India (300−5000); 29 Kuala Lumpur, Malaysia (urban average 2100 pg m −3 ) 46 as well as other urban sites in Mexico City, Mexico (2000−4000 pg m −3 ); 26 Bucharest, Romania (2700−3600 pg m −3 ); 10 and Wadowice, Poland (260−2600 pg m −3 ). 30 Notably, plastic and/or garbage burning was identified as an important source of PM 2.5 in many of these studies, particularly those in South Asia, based upon the observed levels of TPB and, in some cases, other plastic burning tracers.…”
Section: Detection and Quantification Of Tpb In Ambient Pm 25mentioning
confidence: 99%
See 4 more Smart Citations
“…The observed TPB levels in Dhaka were similar in magnitude to prior studies in South Asia, including Kathmandu, Nepal (250−2900 pg m −3 ); 19 Lumbini, Nepal (570−4000 pg m −3 ); 20 Raipur, India (80−15 400 pg m −3 ); 45 Chennai, India (300−5000); 29 Kuala Lumpur, Malaysia (urban average 2100 pg m −3 ) 46 as well as other urban sites in Mexico City, Mexico (2000−4000 pg m −3 ); 26 Bucharest, Romania (2700−3600 pg m −3 ); 10 and Wadowice, Poland (260−2600 pg m −3 ). 30 Notably, plastic and/or garbage burning was identified as an important source of PM 2.5 in many of these studies, particularly those in South Asia, based upon the observed levels of TPB and, in some cases, other plastic burning tracers.…”
Section: Detection and Quantification Of Tpb In Ambient Pm 25mentioning
confidence: 99%
“…The specificity of 1,3,5-TPB to plastic burning is supported by numerous studies on the combustion of plastic or waste materials containing plastic (Table S2) and the absence of TPB in combustion emissions from other when plastic is not present. 2,9,10,47 TPB is predominant in the particle phase in the atmosphere, 28 with >90% in the particle phase at elevated temperatures near its emission source. 47 Any loss of TPB (i.e., due to photolysis, multiphase reactions, or oxidation) would underestimate the plastic burning impact on ambient particulate matter.…”
Section: Potential Impacts Of Plastic Burning On Pm 25 In the Usa And...mentioning
confidence: 99%
See 3 more Smart Citations

Noxious waste burning

Jancsek-Turóczi,
Hoffer,
Bozó
et al. 2021